Pathways in bacterial and archaeal communities dictated by ammonium stress in a high solid anaerobic digester with dewatered sludge. (October 2017) - Li, Ning; He, Jin; Yan, Han; Chen, Sisi; Dai, Xiaohu
Highlights: Metagenomic comparisons of microbial profiles under ammonium stress were conducted. The microbes showed higher abundance in ammonium-related genes under ammonium stress. The reduction of some amino-acid-related genes was observed under ammonium stress. No enhancement of hydrogenotrophic pathways was observed under ammonium stress. Abstract: Metagenomic comparisons of microbial profiles were conducted to investigate differences between the samples from steady (Day 42), ammonium-adjusting (Day 63), and ammonium-stressed (Day 102) periods during the 110-day operation of a high solid anaerobic digester of sewage sludge. Comparing to the steady period, biogas production was slightly inhibited after ammonium adjustment, during which the microbes showed higher abundance in 6 of the total 22 ammonium-related genes. In addition, among the 19 amino-acid-related genes, 9 genes involved in amino acid generation and utilization were reduced, which partially revealed the reason of deterioration of volatile solids (VSs) degradation following ammonium stress. Furthermore, although the acetoclastic pathway was to some extent inhibited with the decrease of biogas amount and content, no enhancement of genes involved in hydrogenotrophic methanogenesis was observed, elucidating the distinct role of ammonium stress in directing bacterial community structure toward the enhanced syntrophic acetate oxidation reaction.